Business Intelligence Systems Adoption: A Systematic Literature Review - Al-adimi, Amira; Ghilan, Mokhtar Mohammed; Yousef, Walid (Sana'a University, 2024)
Even though business intelligence (BI) systems are widely used by organizations across all industries, they frequently fail to yield the expected benefits because the critical success factors (CSFs) that guarantee effective adoption are not considered. Giving this field more scholarly and practical attention is essential. The purpose of this study is to identify and rank the CSFs that influence the adoption of BI. This research employed the systematic literature review methodology. The study analyzes and synthesizes 64 relevant studies to address the CSFs influencing BI adoption. The findings indicate that organizational and technological factors are the most important factors. The study also analyzes the importance of the CSFs. Finally, the study finds that top management support, organizational readiness, clear vision, information/data quality, system integration, IT infrastructure, competitive Pressure, and change management influence BI adoption.